Phenomenon of Hetmanate in context of European press: Ivan Mazepa and Ukraine on pages of French-language Gazette d'Amsterdam in 1708 - Бачинська, Олена Анатоліївна; Бачинська, О. А.; Bachynska, Olena A.; Іванова, Наталія Георгіївна; Іванова, Н. Г.; Ivanova, Nataliia H.; Марчук, Ірина Петрівна; Марчук, І. П.; Marchuk, Iryna P. (Kyiv : Subscription Agency “Ukrinformnauka”, 2025)
The purpose of the research. The analysis of the formation of the image of Ukraine-Hetmanship in the European information space of the 18th century through the reports on the pages of the French-language edition Gazette d’Amsterdam (1708). Methodology. The research is based on the interdisciplinary approach, which allows reconstruction of the content of the newspaper reports and evaluation of the impact of this information on theimage of Ukraine in Europe: identification and classification of historical sources (46 newspaper reports for 1708 that cover events in Ukraine); linguistic analysis (description of the peculiarities of the use of Ukrainian onyms); critical and contextual analysis of the texts (assessment of the political and social accents of that time, factual content, possible political manipulations, propaganda components, etc.) with elements of quantitative analysis (accounting for the frequency of key concepts and their chronological distribution, etc.). Scientific novelty. The research for the first time revealed the informative possibilities of the French-language mass media source Gazette d’Amsterdam, 1708, in covering military and political events in Ukraine-Hetmanship. From a historical point ofview, it is demonstrated that in the European press of the beginning of the 18th century Ukraine was considered as a geographical region and as a political entity with the strategic importance. The role of Ukrainian Cossacks and Hetman Ivan Mazepa in international politics is highlighted. The media tools for constructing the image of Ukraine at the beginning ofthe 18th century are demonstrated. In a philological sense, the use of proper names (Ukraine, Kiowie /Kiovie, Dnieper/Dniper, Boristhene/Boristene, Cosaques, etc.) is analyzed in the military-political context, which outlines the evolution of these onyms in the international information space. Conclusions. The Ukrainian events of 1708 have been covered for the firsttime due to the materials of the Gazette d’Amsterdam. The role of Ivan Mazepa and Ukrainian Cossacks in the international discourse is revealed. The formation of the “image of Ukraine” in the Western press of the 18th century is analyzed. Geographical centers for the dissemination of the information about Ukraine were established and it was traced how it circulated in the European space.
Bachynska O. Phenomenon of Hetmanate in context of European press: Ivan Mazepa and Ukraine on pages of French-language Gazette d'Amsterdam in 1708 / O. Bachynska, N. Ivanova, I. Marchuk // Manuscript and Book Heritage of Ukraine. – Kyiv : Subscription Agency “Ukrinformnauka”, 2025. - 2. - Р. 56–92. URL: https://doi.org/10.15407/rksu.37.056
Keywords: the French-language Gazette d’Amsterdam (1708); formation of the image of Ukraine; Ukraine-Hetmanship; Hetman Ivan Mazepa; Ukrainian Cossacks